Pengaruh Angka Harapan Hidup, Rata – Rata Lama Sekolah dan Tingkat Partisipasi Angkatan Kerja Terhadap Pertumbuhan Ekonomi Kabupaten Tapin - Herlinda Hesti Maulida; Muhammad Saleh (JIEP: Jurnal Ilmu Ekonomi dan Pembangunan, 2023)
The research indicate the effect of labor force participation rate, life expectancy and average length of schooling on the economic growth in Tapin district. The secondary data used is quantitative type received from central bureau of statistics in Tapin district from 2004 to 2020. The data in question is the average length of schooling, economic growth, labor force participation rate and llife expectancy. The research uses the ordinary least square method using time series data from 2004 to 2020 by classical assumptions test and hypothesis testing.The research partially shows that labor force participation rate does not significantly effect economic growth, which partially effect economic growth in Tapin regency is life expectancy and average length of schooling. Three independent variables simultaneously positive and significant impact on economic growth in Tapin regency, the biggest influence on economic growth is variable average length of schooling.